Evaluation of herbicide mixtures and manual weed control methods in maize (Zea mays L.) production in the southern guinea agro-ecology of Nigeria - Imoloame, E.O. (Journal of Tropical Agriculture, 2017)
Field trials were conducted in 2015 and 2016 cropping seasons to evaluate some herbicide mixtures and manual weed control method in the production of maize in the southern Guinea savanna of Nigeria. The experiment consisted of 10 treatments as follows: Metolachlor + atrazine and pendimethlin + atrazine at 1.0 + 2.0, 2.0+2.5, 3.0 + 3.0 kg a.i./ha, metolachlor + atrazine and pendimethlin + atrazine at 1.0 + 2.0 kg a.i./ha plus one supplementary hoe weeding (SHW) at 6 weeks after sowing (WAS), hand weeding at 3 and 6 WAS and a weedy check. These treatments were laid out in randomized complete block design (RCBD) with three replicates. Data collected included weed dry matter, weed density, relative importance value (RIV%) of weed species, leaf area, plant height and grain yield of maize. Also, economic assessment of the weed control methods was carried out. Results showed that metolachlor + atrazine and pendimethalin + atrazine at 1.0 + 2.0 kg a.i./ha plus one SHW at 6 WAS significantly reduced weed infestation and gave higher maize grain yield and economic returns. These methods are therefore recommended to farmers as alternative to two hand weeding at 3 and 6 WAS.